Oxidative stress and free radicals in liver and kidney diseases; an updated short-review - Masoud Amiri (Journal of Nephropathology, 2018)
Context: In normal conditions, liver and kidney act as a supply of internal antioxidants for neutralizing free radicals produced by viruses and internal/external compounds which were processed in the liver and kidney. Evidence Acquisition: PubMed, EBSCO, Embase, Web of Science, directory of open access journals (DOAJ), Scopus, and Google Scholar were searched using keywords of oxidative stress, free radicals, liver diseases, kidney diseases and antioxidant therapy. Results: When the antioxidants of the liver or kidney are low, or when the liver/kidney is under pressure through oxidative insults, the damages produced by free radicals would increase, leading to inflammation and fibrosis. In addition to cytotoxic effect of oxidative stress, it has also a substantial role in modulating of messengers in regulating the functions of cell membrane, with a vital factor for survival. However, there is also some benefits of oxidative stress such as inducing apoptosis to prepare birth canal for delivery or strengthening of biological defense mechanisms during ischemia and physical exercise. Conclusions: There is an important association between diseases related to lifestyle and oxidative stress, as a condition that oxidation may exceed the antioxidant systems of the body with absence of balance between them. Oxidative stress is involved with many diseases such as kidney, liver and lung dysfunctions. Supplementation with vitamins C and E and selenium for four months could improve the balance between antioxidant-oxidant as well as potential slowing down of liver disease progression.